Cetuximab in pancreatic cancer therapy: a systematic review and meta-analysis - Forster, Tobias; Hüttner, Felix; Springfeld, Christoph; Kalkum, Eva; Hackbusch, Matthes; Hackert, Thilo; Diener, Markus K.; Probst, Pascal (Oncology, 2020)
Introduction: The present study evaluated the potential benefit of adding cetuximab to neoadjuvant, adjuvant, or palliative standard therapy for pancreatic cancer. Methods: A systematic literature search was performed in MEDLINE, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL). Only randomised controlled trials (RCTs) investigating the effect of adding cetuximab to standard chemotherapy in pancreatic cancer were included. Evaluated outcomes were overall survival, progression-free survival, objective response, and toxicity. For overall survival and progression-free survival, hazard ratios (HR) with 95% confidence intervals (CI) were chosen as effect measure. For objective response, odds ratios (OR) with 95% CI were used. Analysis was based on a random effects model. Results: After screening 568 publications, a total of 4 RCTs with 924 patients were included. In all trials, patients were adequately randomised with balanced intervention and control groups. There was no significant difference in overall survival (HR 1.04; 95% CI: 0.90-1.19; p = 0.60), progression-free survival (HR 1.06; 95% CI: 0.93-1.22; p = 0.36), or objective response (OR 0.99; 95% CI: 0.66 -1.49; p = 0.96) when adding cetuximab to a standard therapy. Toxicity was the same or higher in each of the included trials. According to GRADE, the certainty of the evidence is high. Therefore, adding cetuximab to pancreatic cancer therapy has no clinically relevant benefit. Conclusion: In the presence of no survival benefit, increased toxicity, and higher costs, a decreased cost-benefit ratio compared to the standard care must be suggested. Conducting further RCTs in unselected pancreatic cancer populations is unlikely to change this conclusion.